SYNTHESIS AND ELECTROCHEMICAL PERFORMANCE OF SILICONE NANOWIRE INTEGRATED POLYANILINE FOR ANODE MATERIALS OF LITHIUM ION BATTERIES - Eldona, Calvin
Theoretically, silicon's large specific capacity makes it a promising lithium-ion battery anode material. Unfortunately, during charge discharge, silicon suffers up to 300 % of volume changes. An excessive solid electrolyte interface layer is formed as a result of the anode cracking and crumbling. Silicon's limited conductivity can also hinder the process of lithiation/delithiation. As a result, charge-discharge stability and capacity may be compromised. Forming silicon nanowire structures and covering them with conductive polymers can solve these issues. Using the Metal Assisted Chemical Etching approach, silicon nanowires were created using an silver (Ag) catalyst. In order to achieve the best nanowire structure and procedure, the etching time was optimized. Polyaniline polymerized by the oxidative polymerization method was applied to silicon nanowires treated for 120 minutes on p-type silicon wafers. Silicon nanowires with a height of 14 ?m were characterized by Scanning Electron Microscope and found to have polyaniline coatings on their surfaces. The Fourier-Transform Infrared Spectroscopy and X-Ray Diffraction analyses revealed the formation of polyaniline in the silicon nanowire samples without the presence of contaminants. After that, a lithium ion half-cell battery is assembled using the silicon nanowire-polyaniline anodes. EIS and Battery Analyzer were used to evaluate the anode's electrochemical performance. Electrochemical Impedance Spectoscopy (EIS) showed that anodes made of silicon nanowires and polyaniline can boost the battery's conductivity. An anode made of silicon nanowires and polyaniline can sustain its capacity up to a current of 2 mA/cm2 while testing the battery's rate capabilities. The electrochemical performance of lithium ion batteries can be improved by the creation of silicon nanowire structures and the application of polyaniline coating.